Single dose antibiotic prophylaxis in planned surgical procedures in Gwalior - Chandrakala Dutt; Abha Shukla; R.D. Dutt (International Journal of Medical Research and Review, 2015)
Introduction: The aim of present study was to prevent the development of the surgical wound infection.Design: Prospective study.Methodology: Study was conducted in surgical ward of J.A. Group of Hospitals, Gwalior, MP, India from May 2014 to April 2015. Study was consisting a total of 125 patients admitted in surgical ward. Statistically - SSPS - 10 systems was applied for study.Results: A total of 125 patients were studied under five group depending on the antibiotics. A, B, C, D groups were given only a single dose of antibiotics while group E was given full course of antibiotics during preoperative, intraoperative and postoperatively. Out of 125 cases, only 5 patients had clinical and bacteriological evidenced of wound sepsis in different groups of single dose antibiotics and one case in group E of multiple doses of antibiotic given. Wound infection rate in clean was 20% in ceftazidine, 12.5% with piperacillin tazobactum and cefoperazone sulbactum and 21.1% in multiple doses group. No infection was reported with amoxycillin - clavulanic acid. Staphylococcus, E. coli and klebsiella were offending agents & anaerobic infections were not found.Conclusion: Single dose of antibiotic prevents the suppression of normal sensitive microbial flora, which is usually seen with multiple doses of antibiotics use. In this way, it helps in keeping the patients infection free without interfering with the naturally inherited immunological status of the patient.